2018
DOI: 10.1093/geronb/gby077
|View full text |Cite
|
Sign up to set email alerts
|

Guilt in Adult Mother–Child Relationships: Connections to Intergenerational Ambivalence and Support

Abstract: Intergenerational ambivalence can be problematic for children because it may increase feelings of guilt. Feelings of guilt are also determined by a lack of reciprocity and by norms about intergenerational support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…Indeed, previous research indicates that people typically respond to intergenerational ambivalence by avoiding contact with their children (Connidis, 2015). The positive aspects of the relationship may cause parents to also feel guilt for not maintaining the relationship (Kalmijn, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous research indicates that people typically respond to intergenerational ambivalence by avoiding contact with their children (Connidis, 2015). The positive aspects of the relationship may cause parents to also feel guilt for not maintaining the relationship (Kalmijn, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have examined the guilt that adult children feel toward their ageing and ill parents (Boll and Filipp 2002;Losada et al 2018). A recent study showed that adult children's feelings of guilt toward their mother are associated with feelings of ambivalence, with imbalances in support exchange, and with norms of filial responsibility (Kalmijn 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The changes associated with increased parents’ age and disability may create challenges for adult children to negotiate tensions with their parents. Moreover, when parents continue to age and become less independent, adult children might experience guilt and worrying emotions toward their parents (Gonyea, Paris, & de Saxe Zerden, 2008; Hay, Fingerman, & Lefkowitz, 2008; Kalmijn, 2018). These emotions may also influence adult children’s behavioral responses to interpersonal tensions with aging parents.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have found that various emotions are associated with moral behaviors (Tangney, Stuewig, & Mashek, 2007) and may have implications for interpersonal relationships (de Hooge, Mohiyeddini, Eysenck, & Bauer, 2013; van Kleef, De Dreu, Pietroni, & Manstead, 2006). Although other emotions, such as anger and hurt, may also be related to conflict strategies (Guerrero & La Valley, 2006), we chose to examine guilt and worry because these two emotions were found to be commonly experienced among adult children who have aging parents (Gonyea et al., 2008; Hay et al., 2008; Kalmijn, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation